Brothers in Arms: The Phenomenon of Complex Suicide Attacks - Ibrahim Shire, Mohammed (Terrorism and political violence, 2022)
Globally, the spread and use of suicide bombing attacks have become a regular occurrence. Suicide terrorism literature focuses primarily on conventional suicide bombing attacks. However, a growing trend has been observed in the adoption of complex suicide attacks. Using Al-Shabaab as a case study, this paper investigates the phenomenon of complex suicide attacks. We explore the tactical differences of complex suicide attacks vis-à-vis simple attacks in terms of its target goal, discriminative lethality, and delivery method. The paper relies on a uniquely constructed dataset of the group’s suicide operations, employing a variety of data collection techniques. The findings reveal that, inter alia, complex suicide attacks reduce civilian casualties compared to simple suicide attacks. Contrary to the group’s intent and official guidelines to target foreign entities; findings illustrate that domestic targets bear the brunt of most complex suicide attacks. These findings have the potential to contribute to counter-terrorism strategies and be adopted by concerned states in order to effectively protect significant loss of lives and destruction of property resulting from suicide terrorism.